A Centrosymmetric Hexagonal Magnet with Superstable Biskyrmion Magnetic Nanodomains in a Wide Temperature Range of 100–340 K. Issue 32 (18th May 2016) - Wang, Wenhong; Zhang, Ying; Xu, Guizhou; Peng, Licong; Ding, Bei; Wang, Yue; Hou, Zhipeng; Zhang, Xiaoming; Li, Xiyang; Liu, Enke; Wang, Shouguo; Cai, Jianwang; et al.
Abstract : Superstable biskyrmion magnetic nanodomains are experimentally observed for the first time in a hexagonal MnNiGa, a common and easily produced centrosymmetric material. The biskyrmion states in MnNiGa thin plates, as determined by the combination of in situ Lorentz transmission electron microscopy images, magnetoresistivity, and topological Hall effect measurements, are surprisingly stable over a broad temperature range of 100–340 K.